Changing health behaviors using financial incentives: a review from behavioral economics - Vlaev,I; King,D; Darzi,A; Dolan,P (BMC Public Health, 2019)
BackgroundIncentives are central to economics and are used across the public and private sectors to influence behavior. Recent interest has been shown in using financial incentives to promote desirable health behaviors and discourage unhealthy ones.Main textIf we are going to use incentive schemes to influence health behaviors, then it is important that we give them the best chance of working. Behavioral economics integrates insights from psychology with the laws of economics and provides a number of robust psychological phenomena that help to better explain human behavior. Individuals’ decisions in relation to incentives may be shaped by more subtle features – such as loss aversion, overweighting of small probabilities, hyperbolic discounting, increasing payoffs, reference points – many of which have been identified through research in behavioral economics. If incentives are shown to be a useful strategy to influence health behavior, a wider discussion will need to be had about the ethical dimensions of incentives before their wider implementation in different health programmes.ConclusionsPolicy makers across the world are increasingly taking note of lessons from behavioral economics and this paper explores how key principles could help public health practitioners design effective interventions both in relation to incentive designs and more widely.